The extent to which elementary school teachers use active learning strategies in teaching mathematics.: A descriptive study from the point of view of primary school teachers in the city of Jijel - Debbache, Nour el Houda; Hadid, Youcef (Journal of Human Sciences, 2022)
The study aimed to identify the degree to which primary school teachers use strategies based on active learning in teaching mathematics, and the researcher used the descriptive and analytical approach, where the study was applied on a sample of (24) teachers distributed over four primary schools in the state of Jijel. The researcher has prepared a questionnaire that was prepared as a tool for the study. It consisted of (31) paragraphs, and the validity and reliability of the tool was confirmed, and the study reached the following results: The main hypothesis. All the proposed hypotheses were also fulfilled in the study, where it came to a high degree, similar to the fourth hypothesis, which is related to the project’s learning strategy, which came with a moderate degree. ;The study also found that there were no statistically significant differences in the degree of use of active learning strategies by elementary school teachers in mathematics education due to years of experience and academic qualification. The study ended with a set of recommendations calling for the need to employ active learning strategies in teaching mathematics in particular and different subjects in general and for all levels .